Analysis of Student Errors in Solving Mathematics Problems Based on Watson's Criteria on the Subject of Two Variable Linear Equation System (SPLDV) - Hastuty Musa; R. Rusli; Ilhamsyah; A. Yuliana (EduLine: Journal of Education and Learning Innovation, 2021)
The purpose of the study was to describe the types of student errors and the factors that caused students to make mistakes in solving a two-variable system of linear equations based on Watson's criteria for class VIII MTs Pattuku. This type of research is descriptive research using a qualitative approach. The subjects in this study were students of class VIII MTs Pattuku then chose 3 subjects to be interviewed who had the most types of errors based on Watson's criteria. The research instrument used was a diagnostic test consisting of 3 questions about a two-variable linear equation system and interview guidelines. From the results of this study, it shows that there are no students who make mistakes in missing data (committed data) and indirect manipulation (undirected manipulation). 16% made incorrect data errors (innapropriate data), 40% made incorrect procedural errors (innapropriate procedure), 68% made an omitted conclusion error, 24% made a response level conflict error, 36% made mistakes in the skill hierarchy problem, and 48% made mistakes other than the 7 categories above (above other).